1978
DOI: 10.1007/bf01072352
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative intestinal motility in dogs and sheep

Abstract: Electrical activity of the small intestine was recorded from chronically implanted electrodes in dogs and sheep. The effects of laparotomy and surgical procedures were identified under general anesthesia. Laparotomy induced in both species a complete inhibition of electrical spiking activity during the stage of muscular and peritoneal incision. The inhibitory period due to laparotomy was shorter in dogs than in sheep and in both species less marked at the duodenal level. A secondary period of inhibition (ileus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
26
1
3

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 11 publications
4
26
1
3
Order By: Relevance
“…Only a few studies dealing with intraoperative electromyographical activity can be found in literature [3,8]. McIntyre and Bueno reported a loss of spike activity during open surgery in dogs and sheep [3,8].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies dealing with intraoperative electromyographical activity can be found in literature [3,8]. McIntyre and Bueno reported a loss of spike activity during open surgery in dogs and sheep [3,8].…”
Section: Discussionmentioning
confidence: 99%
“…immediately after vagotomy in sheep. We do not think that these immediate changes are effects of surgery per se since m.m.c.s are seen at their normal frequency within 24 h of surgery in this species (Bueno, Fioramonti & Ruckebusch, 1978). In the first few days after vagotomy r.s.a.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of bursts is similar to that observed in the antrum of the guinea-pig, rat, in the abomasum of ruminants and in the small intestine of all species (Gonella, 1978). Recording sessions were undertaken 3-4 d post-operatively in order to avoid the period of paralytic ileus commonly observed after abdominal surgery (Bueno, Fioramonti & Ruckebusch, 1978;Abrahamson, Glise & Glise, 1979). The frequency of bursts varied over a wide range up to 4/min as also reported in pigs (Laplace, 1972) and in the abomasum of ruminants (Van Bruchem, 1977;Madhloum, 1982).…”
Section: Discussionmentioning
confidence: 99%